EFEKTIVITAS MODEL COOPERATIVE LEARNING TIPE STAD PADA MATERI SPLTV DI KELAS X SMA - Ayu Lestari; Agung Hartoyo; Dian Ahmad BS (Universitas Tanjungpura, 2019)
AbstractThis research aimed to know the effectiveness of the Cooperative Learning model of the Student Team Achievement Divisions (STAD) type in the material SPLTV in class X of SMA Negeri 5 Pontianak. As for this research in terms from four aspects, among others: Implementation of learning, students activities, completeness of learning students outcomes, and responses of students. The research method used was the experimental method, with a pre-experimental design. The research sample is students in class X IPA 3. Based on data analysis that reviewed four aspects, the results were (1) the implementation of learning management was categorized well with an average score of 3.2. (2) The activities of students are classified as active, namely 71%. (3) The learning outcomes of students in a classical manner are 29 students or 83% who achieve minimal completeness. (4) The response of students is in the very positive category, which is 88%. The conclusion of this research was that the effectiveness of the Cooperative Learning model of the Student Team Achievement Divisions (STAD) type is effective to be applied to in the material SPLTV in class X SMA 5 Pontianak. Keywords: Cooperative learning model, STAD type, System of linear equations three variables